Evidence of maternal vascular malperfusion in placentas of women with congenital heart disease. (January 2022) - Rodríguez-Soto, Ana E.; Pham, Donna; Tran, Tracy; Meads, Morgan; Stanley, Valentina; Melber, Dora; Lamale-Smith, Leah; Zhang-Rutledge, Kathy; Rakow-Penner, Rebecca; Alshawabkeh, Laith; Parast, Mana M.; Contijoch, Francisco
Highlights: Women with congenital heart disease (CHD) deliver small babies and placentas. Maternal CHD was associated with a high prevalence of pre-eclampsia. Their placentas have evidence of maternal vascular malperfusion and no vasculopathy. Cardiovascular dysfunction due to CHD may impact placental development and consequently fetal growth.